Micro-transplantation in an elderly patient with very high risk MDS:A case report and literature review - Kangli Wu; Mingsuo Liu; Yajun Wu; Qiulian Luo; Jin Chen; Wanling Xu; Xixi Yang; Piaoru Hong; Zhigang Qu (Leukemia Research Reports)
Introduction: The prognosis of patients with myelodysplastic syndromes (MDS) (very high risk) is poor.HLA-mismatched allogeneic T-cell infusion which is called micro-transplantation can not only shorten the time of bone marrow suppression, but also improve the treatment response of patients. Case presentation: A 74-year-old woman presented with fatigue and showed pancytopenia on routine blood count. She was diagnosed with MDS (very high risk) after bone marrow examination,then she received 4 cycles of micro-transplantation. The progression-free survival was 22 months and overall survival was 33 months. Discussion: The patient showed good tolerance to micro-transplantation with manageable toxicities and short myelosuppression time.